MENGENALI KEMUNGKINAN PENERAPAN POST MODERN PERSPECTIVE PADA ADMINISTRASI PUBLIK - Emma Rudy, Galih Muharam Hidayat (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2011)
Postmodern Perspectives it is viewed as a POSMO,it is one of the evolution Theory, was born in 1984 by Jean-Francois Lyotard, Postmodernist thought is an intentional departure from modernist approaches that had previously been dominant.The term “postmodernism'' comes from its critique of the ''modernist'' scientific mentality of objectivity and progress associated with the enlightenment, these movement , modernism and postmodernism are understood as cultural to refer to apoint of departure for work of literature, architecture, cinema., as well as in marketing and business. An in the interpretation of law, culture, and religion in the late 20 th and early 21 st centuries. Indeed, postmodernism, particularly as an academic movement, can be understood as a reaction to modernism in the humanities, where as modernism was primarily concerned with the principles such as identity, unity, authority and certainly, postmodernism is often associated with difference, plurality, textuality and skepticism.